Analysis of the passing distance of professional futsal players in the Indonesia Pro Futsal League - Iqbal Doewes, Rumi; Elumalai, Gunathevan; Hartini Azmi, Siti (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The study purpose was to analyze the passing distance of professional futsal players in the Indonesia Pro Futsal League. This cross-sectional study was carried out in the final match of the 2021 Indonesia Pro Futsal League. All players except the goalkeeper were analyzed. We measured the distance of the passes made. Movie Maker software was used for cutting videos of every passing movement and Kinovea software was used for passing distance analysis. This study stated that in maintaining the ball possession, entering the opponent’s defense, and trying to score goals, players can perform various types of passes such as short, medium, and long passes. The results showed that the average passing distance was 3.58 meters for the short pass, 7.46 meters for the medium pass, and 14.47 meters for the long pass. This futsal passing distance analysis can be used as a basis for passing mastery exercises. Therefore, the coach can plan passing training programs with specific distances and maximize the passing accuracy of the players.